Effects of Changes in Production on Stability of Mayonnaise - Paananen, Outi (fi=Turun yliopisto|en=University of Turku|, 2018)
The main aim in this study is to investigate the stability and quality of mayonnaise products with special emphasis on how the changes in production affect the stability and quality of mayonnaise products. The main focus is to analyze the mayonnaise samples with selected analysis to understand effects on the changes in production. Mayonnaises are produced by Saarioinen Oy in Huittinen. Mayonnaises are analyzed fresh and after 2-week incubation in 37 °C. The analysis used in this work study the oxidation products: peroxide value, anisidine value and the acid value, chemical structure of fatty acids: gas chromatography, physical structure of the samples: rheology measurements: viscosity, thixotropic and oscillatory measurements. To support the analysis and measurements sensory evaluations are carried out to link the instrumental analyses to sensory changes. The main results in this study is that the changes in production did not affect the mayonnaises much. The biggest difference between the samples were the oxidation level of the incubated samples compared to fresh samples. The oxidation level in incubated samples after the changes in production were lower than in the mayonnaises made before the production changes. In conclusion the mayonnaises can be produced with different techniques to achieve the nearly same quality mayonnaise.